Exploring relationality in African knowledge systems as a contribution to decoloniality in sustainability science - Melanie Carstens; Rika Preiser (Ecosystems and People)
The current solutions offered by Western sustainability science to address prevailing global environmental destruction and social injustice are still largely embedded in the Western knowledge system established by colonisation, limiting the efficacy of these solutions for a large part of the planet. Conversely, it may be reasonable to imagine that the concept of relationality is beneficial in all cultures and knowledge systems. Relationality, elementally referring to a web of relationships, as considered from an African Indigenous and local knowledge perspective, could play an important role in decolonising Western sustainability science. Two valuable approaches, namely ubuntu (humanness) and ukama (relatedness), as predominantly observed in southern Africa, are essentially immersed in human-nature relationality. This type of relationality considers everything as interconnected, and therefore that nothing happens in isolation, and that the well-being of humans is inextricable from the well-being of nature. The way relationality is approached in African Indigenous knowledge systems is inclusive, holistic and perpetual, broadening its usefulness to a large audience, making it a sensible contributor to decoloniality in sustainability science. A collective knowledge could emerge, including cooperative, multidirectional interactions with different types of information from diverse human and non-human sources, increasingly eradicating the relational divide among knowledge systems caused by persistent colonial discourse and attitudes.